2016
DOI: 10.1159/000445079
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Raman Microspectroscopy: Intra- and Intersubject Variability of Stratum Corneum Spectral Markers

Abstract: Background: In vivo Raman spectroscopy is a powerful tool for real-time analysis and in situ evaluation of tissues such as the skin. The efficiency of this technique has been widely demonstrated as a label-free method for in vivo evaluation of the skin. The aim of this study is to gather information about inter- and intra-individual variations in the spectral descriptors of water content and structure, organization of the lipid barrier and structure of proteins in the stratum corneum (SC). Methods: In vivo SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Slight inter-individual variations of the Raman spectral features were recently reported by Quatela et al [69] which is confirmed in the present study. In order to improve readability of Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Slight inter-individual variations of the Raman spectral features were recently reported by Quatela et al [69] which is confirmed in the present study. In order to improve readability of Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For a detailed analysis of the total fluorescence, a wavelength-dependent light throughput of the detecting optics, as well as the detector sensitivity, would have to be taken into account. 58 Because of scattering, absorption, and anisotropy propagation, the total intensity of the spectra decreases with increasing depth in the skin (data not shown). The Raman/fluorescence ratio clearly increases during the photobleaching process, which is in accordance with previously published data.…”
Section: Discussionmentioning
confidence: 95%
“…Further investigations are necessary to compensate the depth-and wavelength-dependent irradiation and autofluorescence intensities. One approach could be the fluorescence normalization based on the keratin contribution of the recorded Raman spectra, 58 as the keratin distribution within the SC is considered to be homogenous. 41,56 However, for deeper skin layers, the normalization is a very complicated task due to the inhomogeneous distribution of the fluorophors.…”
Section: Photobleaching Decay Parametersmentioning
confidence: 99%
“…The detection level of the investigated product with respect to its Raman spectra was determined by performing dilution assessments in dilutions of 1:10, 1:100, and 1:1000 in octyl dodecanol. This was necessary to also compensate for the restriction and limits of intra‐ and inter‐subject variability of stratum corneum spectral markers . Furthermore, the noise signal of the fitment model at Baseline was also deducted.…”
Section: Discussionmentioning
confidence: 99%
“…This was necessary to also compensate for the restriction and limits of intra-and inter-subject variability of stratum corneum spectral markers. 26 Furthermore, the noise signal of the fitment model at Baseline was also deducted.…”
Section: Min Baselinementioning
confidence: 99%